Job Satisfaction of Women Employees: with Special Reference ‎to Employees in Infopark Kochi, Kerala - K N , Rahanaz; V, Dr. Sudha (International Journal of Accounting and Economics Studies, 2025)
The task of women includes going through an emotional change. Today, women are present in all fields alongside men, whether it’s in ‎the home or the workplace. Working women are not unique and are currently counted as an essential piece of the functioning power. Indian ‎affiliation has encountered a constant growth in the number of women employees, and this case will certainly move on within the destiny too. ‎A flourishing human asset is one of the keys to thinking about victory affiliation. Forgot, this factor is essential for the body of workers to ‎have a tremendous level of fulfillment. Work-life styles are one of the considerable portions of our ordinary workouts, which causes a variety ‎of Stress. ‎ Furthermore, Stress is what’s occurring, making pointless intellectual or physiological requests on an individual. This study includes 150 ‎selected samples, and they were collected randomly. Their work-life balance, satisfaction, and their relations are carefully examined in this ‎study, which also analyzes the various stress factors that affect their WLB. This study detailly the satisfaction level of working ‎women, work stress, and the work-life balance‎.